Exploration of aerosol-precipitation relationships under different climate regimes in China - Yuanyuan Xiao; Jun Zhang; Jingxuan Zhu; Qiang Dai (GIScience & Remote Sensing)
Aerosols influence cloud and precipitation formation through Aerosol-Radiation Interaction and Aerosol-Cloud Interaction, thereby influencing rainfall patterns. Our study analyzed the relationship between aerosols and precipitation in China by remote-sensing observations, focusing on both precipitation magnitude and microphysical characteristics. The aerosol data were obtained from the second Modern-Era Retrospective analysis for Research and Applications (MERRA-2), the precipitation data were sourced from Integrated Multi-satellitE Retrieval for Global Precipitation Measurement (GPM-IMERG) and rainfall microphysical data were collected from the GPM Dual-Frequency Precipitation Radar (GPM-DPR). The total aerosol and five types of aerosols (two natural types and three anthropogenic types) were analyzed in relation to precipitation over the period 2015–2020. Aerosols were categorized into “clean” and “polluted” groups based on their concentrations. The spatial distribution of average rainfall for the clean and polluted groups was analyzed on three time scales (annual, summer, and winter). The results indicated that different types of aerosols present varying effects on rainfall, with natural aerosols exhibiting higher average rainfall in “clean” conditions, while anthropogenic aerosols demonstrate higher average rainfall in “polluted” conditions, especially in humid areas. Additionally, we observed that aerosol concentrations can modify rainfall microphysics, affecting the size and concentration of raindrops. By comparing Dm (the mass-weighted diameter of a raindrop) and Nw (the concentration parameter) under different aerosol conditions, it was found that Dm was significantly larger in summer than winter and in polluted than clean conditions. Nw exhibited slightly higher values in clean conditions. Overall, our findings suggest that enhanced aerosol concentrations intensify rainfall and modify rainfall microphysics, which may be useful in further investigating the principles of how aerosols affect precipitation.